A place at the table [videorecording (DVD)] - Silverbush, Lori; Silverbush, Lori; Jacobson, Kristi, 1971-; Jacobson, Kristi, 1971-; Bridges, Jeff, 1949-; Colicchio, Tom; Burnett, T-Bone (Magnolia Pictures ; [Distributed by] Ro*co Films Educational, 2013)
50 million people in the U.S. - one in four children - don't know where their next meal is coming from, despite our having the means to provide nutritious, affordable food for all Americans. Directors Kristi Jacobson and Lori Silverbush examine this issue through the lens of three people who are struggling with food insecurity: Barbie, a single Philadelphia mother who grew up in poverty and is trying to provide a better life for her two kids; Rosie, a Colorado fifth-grader who often has to depend on friends and neighbors to feed her and has trouble concentrating in school; and Tremonica, a Mississippi second-grader whose asthma and health issues are exacerbated by the largely empty calories her hardworking mother can afford.